มีดตัดพิดเศษสำหรับวัสดุที่กัดขึ้นรูปได้ยาก - ศรัณย์ กีรติหัตถยากร (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To present a new design of cutting tool called driven rotary tool in which the cutting edge of a round insert rotates about its axis. Rotary tool use the modified Hybrid CNC milling machine to control the movement and cutting condition.Cylindrical stainless steel 316L turning experiments at cutting speed 50-90 m/min, depth of cut 0.4 mm, feed rate 0.2 mm/rev and cutting speed ratio 0.4-1.4 are conducted using the driven rotary tool and stationary tool with the same insert for comparison. Results show that chips from driven rotary tool are thinner than chips from stationary tool and cutting temperature of driven rotary tool is lower than stationary tool.In addition, driven rotary tool extends insert’s tool life up to 18 times longer than stationary tool. These results show that rotary tool is more effective than stationary tool and suitable for hard-to-cut material in rough machining process.